Sulfate groups position determines the ionic selectivity and syneresis properties of carrageenan systems. (1st January 2023) - Elmarhoum, Said; Mathieu, Sophie; Ako, Komla; Helbert, William
Abstract: The salt sensitivity and selectivity feature of α-carrageenan (α-Car) were investigated and compared with κ-carrageenan (κ-Car) and iota-carrageenan (ι-Car). These carrageenans are identified by one sulfate group on the 3, 6-anhydro-D-galactose (DA) for α-Car, D-galactose (G) for κ-Car and on both carrabiose moieties (G and DA) for ι-Car. The viscosity and temperature, where order-disorder transition have been observed, were greater in presence of CaCl2 for α-Car and ι-Car compared with KCl and NaCl. Conversely, the reactivity of κ-Car systems were greater in presence of KCl than CaCl2 . Unlike κ-Car systems, the gelation of α-Car in presence of KCl was observed without syneresis. Thus, the position of sulfate group on the carrabiose determines the importance of counterion valency too. The α-Car could be a good alternative to κ-Car to reduce the syneresis effects. Graphical abstract: Unlabelled Image